2014
DOI: 10.1007/s11920-014-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy in the Treatment of Perimenopausal Depression

Abstract: The menopause transition is associated with a two to fourfold increased risk in major depressive disorder (MDD) and clinical elevations in depressive symptoms. While the pathophysiological mechanisms underlying this increased risk remain uncertain, ovarian hormone fluctuation is believed to play a role. To the extent that this is the case, hormone replacement therapy (HRT), through its hormone-stabilizing effects, represents a viable antidepressant treatment. The current review summarizes the most recent liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…A possible explanation for the interaction might be that in women aged 60 years or younger, hormonal fluctuations, as seen during the menstrual cycle and perimenopause, rather than aortic stiffness could predispose them to depression. 34 Reproductive hormones are also thought to have a protective effect on the vasculature, especially before menopause, 15,16 thus further diminishing the association between cfPWV and depression in women. Exogenous hormone supplementation, such as hormone replacement therapy or contraception, could also be a confounder; however, in our study use of such medication was infrequent and did not affect the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the interaction might be that in women aged 60 years or younger, hormonal fluctuations, as seen during the menstrual cycle and perimenopause, rather than aortic stiffness could predispose them to depression. 34 Reproductive hormones are also thought to have a protective effect on the vasculature, especially before menopause, 15,16 thus further diminishing the association between cfPWV and depression in women. Exogenous hormone supplementation, such as hormone replacement therapy or contraception, could also be a confounder; however, in our study use of such medication was infrequent and did not affect the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…The review did not include intervention studies, neuroendocrine studies, animal models, or studies of postmenopausal women. These domains are clearly important for understanding the development of depression around menopause but are beyond the range of this review and are examined elsewhere [14,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…19 Emerging evidence indicates that hormone replacement therapy, particularly during the perimenopausal period, can be effective in the prevention of postmenopausal depression in women. 20 Another study involving female macaques examined relocation stress-sensitive alterations in their menstrual cycles and showed depressionrelated behaviours and reductions in the function of the brain serotonin system. 21 In this light, a recent study has indicated that women who reported using an oral contraceptive (especially monophasic contraceptives) showed reduced rates of major depression and anxiety compared with nonusers, 22 suggesting that moderating the cycling of estrogen may be protective.…”
mentioning
confidence: 99%